2004
DOI: 10.1103/physrevd.70.097505
|View full text |Cite
|
Sign up to set email alerts
|

Landau-gauge condensates from the quark propagator on the lattice

Abstract: We compute the dimension-2 condensate, A 2 , and dimension-4 mixed condensate, q / Aq , from the recent quenched lattice results for the quark propagator in the Landau gauge. We fit the lattice data to the Operator Product Expansion in the "fiducial" region 1.2 GeV ≤ Q ≤ 3 GeV. Our result for the dynamical gluon mass at the scale of 10 GeV 2 is mA = 600 − 650 MeV, in agreement with independent determinations. For the mixed Landau gauge condensate of dimension-4 we get αs qg / Aq = (−0.11 ± 0.03) GeV 4 . This v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 32 publications
10
97
1
Order By: Relevance
“…Furthermore, the gluon masses claimed above agree well with the estimate of the gluon mass from the gluon condensate A 2 obtained in [29], where the value 625(33) MeV was obtained, and is well within the interval of values estimated from phenomenology [4].…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, the gluon masses claimed above agree well with the estimate of the gluon mass from the gluon condensate A 2 obtained in [29], where the value 625(33) MeV was obtained, and is well within the interval of values estimated from phenomenology [4].…”
Section: Resultssupporting
confidence: 75%
“…[3], we study 60 more at β = 2.1 (aµ l = 0.002) and three new ensembles of 50 configurations at β = 1.9 and aµ l = 0.003, 0.004, 0.005 to peform a chiral extrapolation for the ratios of lattice spacings. We get: a(2.1, 0.002)/a(1.9, 0) = 0.685 (21). The lattice scale at β = 1.9, 1.95, 2.1 is fixed by ETMC through chiral fits to lattice pseudoscalar masses and decay constants, where 270 < ∼ m PS < ∼ 510 MeV, that are required to take the experimental f π and m π at the physical point [8,9]; e.g.…”
Section: The Strong Coupling In Taylor Schemementioning
confidence: 99%
“…(2) is dominated by the first correction introduced by the nonvanishing dimension-two Landau-gauge gluon condensate [16][17][18][19][20][21], where the Wilson coefficient is applied at the O(α 4 )-order. In the previous methodological paper [3], we provided with a strong indication that the OPE analysis is indeed in order: it was clearly shown that the lattice data could be only explained by including non-perturbative contributions and that the Wilson coefficient for the Landau-gauge gluon condensate was needed to describe the behaviour of data above p 4 GeV and up to p 7 GeV (see next Fig.…”
Section: The Wilson Ope Coefficient and The Higher-power Correctionsmentioning
confidence: 99%
“…After it turned out more recently that the Landau-gauge value of A 2 corresponds to a more general gauge-invariant quantity, it attracted a lot of theoretical attention [8,9,10,11,12,13,14,15,16,17,18], to quote just several of many papers offering evidence that A 2 condensate may be important for the nonperturbative regime of Yang-Mills theories. In Ref.…”
Section: Introductionmentioning
confidence: 99%